Adapting the motet(s)? The case of Hé bergier in Oxford MS Douce 308 - Leach, E (Cambridge University Press, 2019)
The present article seeks to further recent discussion of the diversity of the motet in the long thirteenth century by considering a specific, rather unusual example of motet-related materials in a songbook. It examines a two-stanza pastourelle in the songbook that forms part of Oxford, Bodleian Library MS Douce 308, and its relationship to a network of related materials in various thirteenth-century motet sources. In so doing, it proposes the ostensibly unlikely scenario that this monophonic song derives from two separate motets that may already have been linked through their shared tenor and possibly also performed together in some way. This article brings the important conclusions of Fred Büttner in regard to these materials to Anglophone scholarship, while nuancing his reasoning in light of more recent scholarly on thirteenth-century motets copied in songbooks.